Improved side-chain modeling by coupling clash-detection guided iterative search with rotamer relaxation - Cao, Yang; Song, Lin; Miao, Zhichao; Hu, Yun; Tian, Liqing; Jiang, Taijiao (Bioinformatics, 2011)
Motivation: Side-chain modeling has seen wide applications in computational structure biology. Most of the popular side-chain modeling programs explore the conformation space using discrete rigid rotamers for speed and efficiency. However, in the tightly packed environments of protein interiors, these methods will inherently lead to atomic clashes and hinder the prediction accuracy. Results: We present a side-chain modeling method (CIS-RR), which couples a novel clash-detection guided iterative search (CIS) algorithm with continuous torsion space optimization of rotamers (RR). Benchmark testing shows that compared with the existing popular side-chain modeling methods, CIS-RR removes atomic clashes much more effectively and achieves comparable or even better prediction accuracy while having comparable computational cost. We believe that CIS-RR could be a useful method for accurate side-chain modeling. Availability: CIS-RR is available to non-commercial users at our website: http://jianglab.ibp.ac.cn/lims/cisrr/cisrr.html. Contact:  taijiao@moon.ibp.ac.cn Supplementary information:  Supplementary data are available at Bioinformatics online.